Can information on school attributes and placement probabilities direct search and choice? Evidence from choice platforms in Ecuador and Peru - Felipe Arteaga; Gregory Elacqua; Thomas Krussig; Carolina Méndez; Christopher A. Neilson (Inter-American Development Bank (IDB), 2022)
This paper evaluates how new information influences families' applications and assignment outcomes in elementary school choice settings. Specifically, using a multi-country RCT based in Tacna, Peru and Manta, Ecuador, we examine the effect of providing personalized information on schooling alternatives and placement risk. We find that applicants who received feedback on placement risk and a suggestion of new schools add more schools to their applications and were more likely to include recommended schools than other alternatives available. Interestingly, the project implemented in Manta, Ecuador had only marginal effects for all outcomes. The main difference across implementations was the inclusion of outreach and information provision through an additional WhatsApp "warning" in Peru, which was not realized in Ecuador. A lower school density seems to have also been a contributing factor to the results observed in the Ecuadorian context.
Keywords: I20; I21; I22; 330; school information; school attributes; direct search; direct choice; choiceplatforms; Ecuador; Peru